2012
DOI: 10.1371/journal.pone.0029877
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding Bromeliaceae: Achievements and Pitfalls

Abstract: BackgroundDNA barcoding has been successfully established in animals as a tool for organismal identification and taxonomic clarification. Slower nucleotide substitution rates in plant genomes have made the selection of a DNA barcode for land plants a much more difficult task. The Plant Working Group of the Consortium for the Barcode of Life (CBOL) recommended the two-marker combination rbcL/matK as a pragmatic solution to a complex trade-off between universality, sequence quality, discrimination, and cost.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 29 publications
6
35
0
Order By: Relevance
“…However, we were able to get high-quality bidirectional sequences with the success rate falling next to rbcL, which is considered the most efficient barcode locus as far as sequence quality is considered. The high quality bidirectional sequence was also obtained by Maia et al in the family Bromeliaceae, where only 2 out of 101 samples failed in generating high quality trnH-psbA bidirectional sequences after the second trial [9]. Except for the low PCR amplification rate of trnH-psbA , our study agrees with the findings of the work reported by Gonzalez et al [6], where they observed that trnH-psbA was the best performing locus for barcoding Amazonian trees.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, we were able to get high-quality bidirectional sequences with the success rate falling next to rbcL, which is considered the most efficient barcode locus as far as sequence quality is considered. The high quality bidirectional sequence was also obtained by Maia et al in the family Bromeliaceae, where only 2 out of 101 samples failed in generating high quality trnH-psbA bidirectional sequences after the second trial [9]. Except for the low PCR amplification rate of trnH-psbA , our study agrees with the findings of the work reported by Gonzalez et al [6], where they observed that trnH-psbA was the best performing locus for barcoding Amazonian trees.…”
Section: Discussionsupporting
confidence: 91%
“…In a recent study, it has been predicted that over half of the estimated 11,000 Amazonian tree species may face a direct risk of extinction [1].Thus, there is an urgent need to carry out an inventory and manage diversity using innovative tools, like DNA barcoding. Significant progress has been made in mapping the Neotropical plants during the last decades [2][5], including studies on DNA barcoding in tree species [6] and other plant species [7][9]. However, such studies on tree species of India are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Other candidates include nuclear ribosomal genes [7]; however, their utility as DNA barcodes may be limited by incomplete concerted evolution, fungal contamination, and amplification failure [3]. Although DNA barcoding using multiple genes has proven successful with high resolution for phylogenetically diverse communities, e.g., Panamian trees (98% species discrimination, [8]), Mesoamerican orchids and Kruger National Park trees (> 90% species identification, [9]), but see Gonzalez et al (< 70% species identification, [10] for Amazonian trees), barcoding studies of single clades have had limited success, e.g., 43.5% species discriminated in Bromeliaceae [11], and 32% in Fraxinus [12]. Alternative candidates for DNA barcodes are low-copy nuclear genes, which have received little attention (i.e., [13]).…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the results of the pairwise distance distribution analysis (Fig. 4), this may be a result of psbA being more conserved than COI, considering that studies in other taxonomic groups have shown conserved genes lead to paraphyletic relationships and unresolved phylogenies (Maia et al 2012).…”
Section: Discussionmentioning
confidence: 99%